Systematic review of pinniped sightings and strandings along the Pacific Coast of Colombia: implications for pinniped conservation - Barragán-Barrera, Dalia C.; Gálvez, Casandra; Bermúdez-Rivas, Christian; Aguirre-Tapiero, María del Pilar; Avila, Isabel Christina; Arévalo-González, Katerin; Acosta-Pachón, Tatiana A. (Aquatic Mammals, 2024)
Sightings of pinnipeds in Colombian waters of the Pacific Ocean have sporadically been reported since 1970. Despite the Colombian Pacific region (CPR) not being within their typical distribution range, six pinniped species—the Galápagos fur seal (Arctocephalus galapagoensis), the Galápagos sea lion (Zalophus wollebaeki), the South American fur seal (Arctocephalus australis), the South American sea lion (Otaria byronia), the Juan Fernández fur seal (Arctocephalus philippii), and the southern elephant seal (Mirounga leonina)—have been recorded in recent times. This study presents an overall systematic review of pinniped sightings and strandings from 1970 to 2023 along the Pacific coast of Colombia, with a total of 68 sightings of 80 individuals. Pinnipeds were recorded most often in 1998 (13 individuals), followed by 2014 (nine individuals); 1997 (eight individuals); 1983 (seven individuals); and 1993, 1996, 2015, and 2020 (with three individuals each year). Most pinniped observations correspond to vagrants—solitary, young individuals sighted on the southern coast of the Colombian Pacific, specifically in Tumaco. Some records of these species appear to be influenced by upwelling events and changes in climatic-oceanographic phenomena (ENSO episodes) in the region. Further monitoring is necessary to determine whether species presence and abundance in the CPR is a response to (1) vagrant behavior of the species, (2) altered habitat use associated with bioecological changes in the species populations, and/or (3) shifts in distribution ranges related to potential new habitat suitability.